(untitled) (Andamios, Revista de Investigación Social, 2008)
This article presents a reflexion on the social function of contemporary artistic practices. The work takes, initially, a position on postmodernism and also reviews the principal philosophical positions that allow us to assert a pragmatic proposal about the aesthetic proposal. By means of the critical analysis of these proposals, the author indicates the aspects that could be taken into account to elaborate a view that allows us to think about the inmanent relations between art and ethics, which is oriented in this work through the concepts of “dialogue”, “knowledge” and “aesthetic experience”.